Constraints and Negotiations to Student Recreational Sport Center Usage - Powers, Samantha L.; Trauntvein, Nate E.; Barcelona, Robert J.; Hartman, Cindy L. (Journal of Amateur Sport, 2019)
Studies have shown that student recreational sports centers offer a variety of benefits to emerging adult students. Previous research has identified the presence of constraints to physical activity and student recreational sports center (SRSC) usage (Flood & Parker, 2014; Stankowski, Trauntvein, & Hall, 2017; Young, Ross, & Barcelona, 2003). However, little research has examined the negotiation strategies which students use to increase their physical activity levels through use of the SRSC. This study focused on the constraints and negotiation strategies which affected both users and infrequent users of the SRSC at a mid-size, public university in the northeastern United States. Results suggested that constraints and negotiation strategies differed significantly between user groups and that several constraints and negotiations predict frequency of visitation to the SRSC. Findings suggest the importance of management actions which help students to create social networks, improve their planning and prioritization, and develop self-efficacy with regard to physical activity at the SRSC.